Investigating the impact of it adoption on innovative performance in small and medium software manufacturing - Ajmi Falih, Mohanaed; Noori Fejer, Hamzah (International Journal of Engineering and Technology, 2018)
The purpose of this study was to investigate the effect of IT adoption on the innovative performance in small and medium software manufacturing companies. This research is an applied and correlational study. The statistical population in this study was 920 employees of small and medium software manufacturing companies and sampling method was simple random sampling method that the sample size for this study was 270 people using Morgan table. In this research, two researcher-made questionnaires were used to collect information. To measure reliability, the Cronbach Alpha Measurement Instrument has been used. About the information technology questionnaire is equal to 0.78 and for the innovative performance questionnaire is equal to 0.78 and since these values are larger than 0.7 which demonstrates the high reliability of the questionnaires. The validity of the questionnaires was verified by the professors. Statistical research methods include structural equations using AMOS software and the results of the research showed that adoption of IT technology has an impact on the innovative performance in small and medium software manufacturing companies in.